Technological Developments in the Perspective of Christianity - Eva Monica Teresa Kodongan; Remegises Danial Yohanis Pandie (CV. Rayyan Dwi Bharata, 2022)
This article will examine and comment on the views of Christianity on the rapid development of theology in currently a very dominant factor in human life, it is expected that an accurate and clear view in addressing the development of technology. The intended perspective is consistent and in line with the Biblical foundation. The author concludes that technology is part of God’s greatness and power through the human mind as His creation. Technology is useful for preserving life as well as being tool to continue the maintenance of God. Technology promises a much easier life, but at the same time the threat to the environment is so open. Thus technology must be approached wisely in accordance with the God’s will.